Peranan Konsultan PMI (Pengendali Mutu Independen) Pada Pelaksanaan Pekerjaan Jalan Tol Manado Bitung - Yolanda Febrianti; Toar U. Y. Pangkey; Shirly S. Lumeno, (Sustainable Construction (SUSCON), 2023)
This study aims to determine how big the role of the PMI consultant (Independent Quality Controller) is in the implementation of the Manado Bitung toll road work. Information about the role of the PMI consultant (Independent Quality Controller) in the implementation of the Manado Bitung toll road works is one of the benefits of this research. This research method uses a quantitative descriptive technique with primary data techniques using a questionnaire whose answers are tested for validity, reliability, normality, simple linear regression, partial test (t-test), coefficient of determination, and other documents needed for this study. Secondary data is data in the form of reports, books, journals, and other documents. The majority of answers to statements about the role of PMI consultants (Independent Quality Controllers) on the criteria of moderate role (BS) by 30%, playing a large role (BB) by 30%, and on the implementation of the Manado Bitung toll road work with the criteria of Agree (S) by 40% become a basis of research findings. The role of the PMI consultant (Independent Quality Controller) in the implementation of the Manado Bitung toll road work, according to the results of the t-test, also shows a t count of 8.348 > t table and a significant value are 0.000 <0.05. This means that H0 is rejected, and Ha is accepted..